Low-toxicity amphiphilic molecules linked by an aromatic nucleus show broad-spectrum antibacterial activity and low drug resistance. Issue 30 (21st February 2019) - Chu, Wenchao; Yang, Yi; Qin, Shangshang; Cai, Jianfeng; Bai, Mengmeng; Kong, Hongtao; Zhang, En
Abstract : Amphiphilic molecules linked by an aromatic nucleus, possessing strong bactericidal activity, high selectivity, less drug resistance, and high in vivo efficacy against MRSA, were developed. Abstract : Amphiphilic molecules linked by an aromatic nucleus were developed that showed high selectivity toward bacteria over mammalian cells, and low drug resistance. A promising compound4g exhibited strong bactericidal activity against a panel of sensitive and resistant bacteria, low toxicity, the ability to reduce cell viability in biofilms, stability in mammalian fluids, rapid killing of pathogens, and high in vivo efficacy against methicillin-resistant Staphylococcus aureus (MRSA).